Economies of the Organizations of Eastern Caribbean States in the 1970's - McIntyre, Arnold M. (ISER Cave HillBB, 1986)
Describes the economies of the OECS countries during the seventies focusing on the severe economic environment faced by these countries during the decade. Examines the functioning of macroeconomic variables such as output, employment, government finances and investment. Surveys macroeconomic activity in the OECS States focusing specifically on growth GDP, government finances, trade, inflation, money supply, and external debt. Discusses the external sector and economic growth and implications for OECS policy.